Pengaruh Kedisiplinan Shalat Berjamaah dan Pemahaman Kultum Terhadap Kecerdasan Spiritual Siswa Kelas VIII Di SMPN 1 Jetis - Sepvia Diana Nopita Sari; Hestu Wilujeng (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
This study aims to analyze the influence of discipline in congregational prayer and understanding of religious sermons (kultum) on the spiritual intelligence of 8th-grade students at SMPN 1 Jetis. Spiritual intelligence is important in shaping students' character and morals. However, several issues were identified, such as tardiness in congregational prayers, preference for sitting in the back rows, and lack of understanding of the messages conveyed in the sermons. This research employed a quantitative correlational non-experimental method with simple random sampling. Data collection was conducted through questionnaires and documentation.The results of the study show that: (1) Discipline in congregational prayer has a significant effect on spiritual intelligence, with the regression equation Y = 16.723 + 0.501X1, a P-value of 0.000 < 0.05, and an R² value of 21.4%; (2) Understanding of sermons also has a significant effect, with the equation Y = 22.301 + 0.341X1, a P-value of 0.000 < 0.05, and an R² value of 23.6%; (3) The combination of discipline in prayer and understanding of sermons has a simultaneous effect on spiritual intelligence with the model Y = 15.702 + 0.307X1 + 0.234X2, a P-value of 0.000 < 0.05, and an R² value of 29.3%. Therefore, improving discipline in prayer and understanding of sermons can enhance spiritual intelligence.